Breeding for Drought Tolerance - International Potato Center (2014)
Breeding for drought-prone environments is truly challenging as adaption to drought can be achieved through drought escape, drought avoidance or drought tolerance. In Mozambique, vine vigor has proved to be an essential and straightforward trait to select for.